Identification of differentially expressed genes related to height increment in oil palm (Elaeis guineensis Jacq.) - Mohamed Azni, Intan Nur Aini (2014)
The effort towards developing dwarf palm population with novel traits has great importance to the oil palm industry, mainly due to the high cost of harvesting fruits from tall palms and crop improvements. Reducing palm height not only brings positive effect on harvesting cost, it will significantly extent the economic cropping cycle. Through the advancement in molecular technologies, identification of potential candidate genes that regulate in dwarfism can be achieved. In this study, six subtracted cDNA libraries were constructed by the Suppression Subtractive Hybridization (SSH) method using spear leaf tissue samples from MPOB Planting Series 1 (PS1) and FELDA P.P.P. Tun Razak (BACKCROSS, AG1) breeding lines. A total of 973 sequences (forward and reverse) were generated from six subtracted libraries. The similarity searches using BLASTX revealed that six clones were identified to be involved in dwarfism based on its putative functions. The gene transcripts encoding for: brassinosteroid biosynthesis-like protein (DWF1),BRASSINOSTEROID INSENSITIVE 1-associated receptor kinase 1 precursor,putative (BRI1), late elongated hypocotyl protein (LHY), gibberellin receptor GID1,putative (GID1), sterol 24-methyltransferase 1 (SMT1) and E3 ubiquitin-proteinigase MARCH6 (E3Ub). These candidate dwarfing genes were reported to be involved in various stages of brassinosteroids (BRs) and gibberellins (GAs) biosynthesis and signaling pathways for plants growth and development. BRs areplant steroids that present in vegetative tissues such as shoot, leaves and stems; pollen grains, anthers and seeds. BRs control diverse physiological processes including cell division and elongation, embryogenesis, fertility, delayed senescence and vascular differentiation. GAs stimulate critical stages in plant growth and development such as plant height, cell wall modification, seed germination,flowering and leaf expansion. Gene validation analysis via qRT-PCR has revealedthe expression levels of each potential candidate dwarfing genes in all tested samples, normalized by two most stable reference genes, manganese superoxide dismutase-like protein (PD569) and hypothetical protein (EA1332). Based on the analysis, higher expression level of BRI1, LHY and SMT1 genes were observed in dwarf palms compared to standard palms with normalized fold-difference of 2.3285,1.5620 and 4.9044, respectively. However, lower expression of DWF1, GID1 and E3Ub were observed in dwarf palms compared to standard palms with normalized fold-difference of 0.8378, 0.7003 and 0.9631, respectively. Statistical analysis using Paired Samples T-Test showed that the expression levels of DWF1, BRI1, LHY,GID1 and E3Ub were not significantly expressed in dwarf palms. However, the SMT1 expression level was highly significant in dwarf palm, AG1-22. The expression profile of SMT1 in all tested samples was carried out using AG1-22 as the control baseline (1.0000 expression levels), where the GOI expression level below 1.0000 indicates as down-regulated; and above 1.0000 is up-regulated. The result showed that the dwarf palm, AG1-12 was up-regulated with 1.3161 expression value. Therefore, SMT1 gene may be potentially useful molecular marker for the screening of dwarf palm planting materials.